Differences in the Form of Presentation between Papillary Microcarcinomas and Papillary Carcinomas of Larger Size. (30th November 2010) - Zafon, Carles; Baena, Juan Antonio; Castellví, Josep; Obiols, Gabriel; Monroy, Gabriela; Mesa, Jordi
Abstract : Papillary thyroid carcinomas (PTCs) with a diameter ≤1 cm are referred to as papillary microcarcinomas (PTMCs). The prognostic factors for PTMCs have not been defined. Different clinical and histopathologic variables were studied in 152 PTCs, including 74 PTMCs and 78 PTCs of larger size. We found that PTMCs are associated with less multifocality (P = .046 ) and bilaterality (P = .003 ), fewer lymphadenectomies (P < .001 ), and a higher rate of incidental tumours (P < .001 ). Moreover, patients with a low aggressive profile were significantly older than the remaining patients (54 ± 13.7 years versus45.8 ± 13.1 years;P = .001 ). In conclusion PTMCs show significant differences compared to PTCs of larger size in the form of presentation. Furthermore, it is possible that the classic risk factors, which are well validated in PTCs, such as age, must be cautiously interpreted in the current increasing subgroup of PTMCs.